Pastoral da Juventude nas ilhas de Abaetetuba-PA: um jeito de ser e fazer - COSTA, Max José Costa e (2019)
The present work intends to make a study on the pastoral care of the youth (PJ) of the parish, our Lady Queen of Peace belonging to the diocese of Abaetetuba-PA. The objective is to investigate the Youth Pastoral in the field and in a particular way in the islands of Abaetetuba seeking to understand its importance in the formation of social leaderships. The work proposal arises from the course of education of the field when, during the field research, former youth pastoral activists were included in the leadership of communities, associations and acting within schools. It is possible to analyze the growing number of young people leaving their communities located in the islands in order to seek a better quality of life in the urban area. In addition, early family formation is another problem to be thought of, consequently a large part of the youth public is absent from integral formation of youth ministry. In the course of the study, the research was carried out through field research with the application of open and closed semistructured questionnaires with qualitative research, taking into account the oral history and analysis of the pastoral documentary records. It is notorious that the subject that passes through the PJ is differentiated, that is why the leaders formed in the youth ministry tend to occupy with efficiency the spaces they occupy in society. It was possible to notice that many militants of the organization theoretically do not know the integral formation and the stages of the pastoral (convocation, initiation, nucleation and militancy). However, when encountering people who have passed through the Youth Ministry and today are people who are fighting for a just and equal society is to realize that a grassroots work beyond formal education is necessary.